Relationship of Dermatoglyphics Pattern and Malocclusion among Individual Visiting a Tertiary Dental Care Center in Kathmandu (Nepal Medical College Journal, 2024)
Dermatoglyphics is used as diagnostic and research tool in many fields including forensics to identify the individuals by forensic experts and in association with various medical conditions. The development of teeth and its associated structures coincide with the development of epidermal ridges during the 6th to 13th week of intrauterine life. This forms the basis for studying the association of dental anomalies with fingerprint pattern, malocclusion being most commonly reported oral conditions and is widely prevalent. Individuals including students and interns within the age group of 18-24 years visiting Nepal Medical College and Teaching Hospital, Attarkhel, Gokarneshwor-8, Kathmandu from April 2024 - June 2024 were included after signing the written consent form. Malocclusion was assessed based on Angle’s classification according to which participants were grouped into Class I, Class II, and Class III malocclusion. The fingerprints of all ten fingers of both the hands of the participants were recorded with ink by using roller method as suggested by Cummins and Midlo. Descriptive statistics was presented in the form of frequency, percentage, mean and standard deviation. Chi square test was done to find out the association of dermatoglyphic pattern with malocclusion using SPSS- 17 software with significance level set at P